The Uniqueness of The Early Childhood Education System in Japan - Budi Mulyadi (IZUMI, 2020)
(Title: The Uniqueness of The Early Childhood Education System in Japan) This study is entitled the uniqueness of the early childhood education system in Japan. The main objective of this research is to find out about some of the uniqueness of the early childhood education system in Japan that is different from other countries. This research is a type of literature study that only relies on data from written sources such as books, journals, articles, and others. Data collection methods used in this study include classification, analysis, interpretation of synthesis and description. From the results of the study, in general, it can be described that the early childhood education system in Japan has much uniqueness. From the results of the study, in general, it can be described that the early childhood education system in Japan has much uniqueness. This uniqueness can be seen in the activities of the beginning of the new school year and how to enter kindergarten, at the entrance ceremony for new students, when doing daily activities in class, when additional activities outside the classroom and when organizing traditional Japanese cultural activities.